Familial Hemiplegic Migraine Type 3 (FHM3) With an SCN1A Mutation in a Chinese Family: A Case Report - Shao, Na; Zhang, Haining; Wang, Xue; Zhang, Wuqiong; Yu, Miaomiao; Meng, Hongmei (Frontiers in Neurology, 2018)
Familial hemiplegic migraine (FHM) is a rare, monogenic, autosomal dominant subtype of migraine, in which three genes, CACNA1A, ATP1A2, and SCN1A, are currently known to be involved. Seldom, the familial hemiplegic migraine type 3 (FHM3) is caused by mutations in SCN1A. Here, we report a rare case of an SCN1A mutation leading to FHM3 in a Chinese family. This case report describes a 62-year-old female patient was admitted to our clinic. She presented with recurrent attacks of hemiplegic migraine. Her symptoms were first suspicious of a transient ischemic attack (TIA), but they were eventually diagnosed as FHM with a c.4495T>C mutation being found in the SCN1A gene. This case highlights that when a patient presents at the clinic with TIA symptoms associated with migraine, the diagnosis of an FHM should be considered and a genetic test is indicated. The identification of SCN1A gene mutations may help us to further understand the FHM pathophysiology.